Auditoria em saúde: revisão integrativa sobre registros de enfermagem - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The health audit can be considered a tool for qualification healthcare and patient safety. It makes viewing and control easier of the work process of health institutions and professionals, through the analysis of documents recording actions and work results. Analyze how records nursing constitute sources of information for health audits. An integrative review of the literature will be carried out with the descriptors: “nursing records”, “forms and records control”, “nursing audits”, “patient care”, “nursing care”. The criteria for inclusion previously defined according to PRISMA are: available free of charge, in full article format, published in Portuguese, English or Spanish. O Exclusion criteria will be not presenting information about nursing records. At Care Audit category highlighted the construction of systems and electronic forms as a way of qualifying the carrying out of specific records of nursing. In the Cost Audit, the control of excess time was possible to from the implementation of the gaps identified in the care audit. It is understood thatnursing records address institutional audit issues by constitute a source of information. These mainly reveal the development of electronic programs and forms on the international scene.
Healthcare audit: integrative review on health records nursing
Keywords: Assistência ao paciente; Cuidados de Enfermagem; Controle de formulários e registros; Auditoria de enfermagem; Nursing care; Registros de enfermagem; Nursing records; Control of forms and records; Audit of nursing; Patient assistance; CNPQ::CIENCIAS DA SAUDE